Effectiveness of climate change education—a meta-analysis - Aeschbach, Vanessa Marie-Jane; Schwichow, Martin; Rieß, Werner (Frontiers in Education, 2025)
Climate change is one of the most pressing issues of our times. Consequently, climate change education (CCE) should prepare students to mitigate the effects of climate change and adapt to its consequences through promoting climate literacy. The present meta-analysis’ aim is to investigate the effectiveness of CCE interventions on climate literacy, including climate related knowledge, attitudes, and behavior. Additionally, we investigated moderator variables that may influence the effectiveness of CCE. We conducted a systematic literature search and selection process following PRISMA guidelines. A total of 6,159 records were identified, of which 53 were eligible for inclusion in the meta-analysis. The data were analyzed using multi-level random effects modelling to pool the effect sizes across all studies. Results revealed a significant medium to large mean effect size for knowledge related outcomes (g = 0.77, 95% CI = 0.58, 0.96), a significant small to medium effect for attitude related outcomes (g = 0.39, 95% CI = 0.17, 0.62), and a small to medium effect for behavior related outcomes (g = 0.36, 95% CI = 0.12, 0.61). Regarding moderator analysis, there were significant effects for the content of the intervention for knowledge related outcomes. For attitudinal outcomes, we found a significant effect for treatment duration and for the teacher who delivered the CCE intervention. Overall, the heterogeneity of the included studies was large, calling for caution when interpreting these results. Our findings highlight that more qualitatively high research about CCE is needed.